2023
DOI: 10.1038/s41405-023-00134-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel caries detecting oral rinse

Abstract: Aim LumiCare™ Caries Detection Rinse (LC Rinse), a starch-based rinse, illuminates active initial caries (positive response) using dental curing light, thus augmenting the dentist’s visual examination. This clinical study investigated if active caries as assessed by the International Caries Detection and Assessment System (ICDAS) were more likely to have positive LC Rinse response than sound surfaces and inactive caries. Methods 25 subjects partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Quantitative laser fluorescence relies on the projection of visible light (ʎ = 600-700 nm, typically from a laser diode) onto suspected caries lesions which is then absorbed by endogenous fluorophores [107,108]. More recently, a caries detecting oral rinse (LumiCare TM ) has been developed which contain proprietary fluorescent starch nanoparticles that allow active initial caries lesions to be detected using a dental curing lamp [109]. Similar to dental photoinitiators, absorption by the endogenous fluorophores or the fluorescent starch nanoparticles leads to excitation of electrons, thermalisation of energy and eventually a return to ground state with the emission of longer wavelength (typically NIR), lower energy radiation.…”
Section: Transillumination and Fluorescencementioning
confidence: 99%
“…Quantitative laser fluorescence relies on the projection of visible light (ʎ = 600-700 nm, typically from a laser diode) onto suspected caries lesions which is then absorbed by endogenous fluorophores [107,108]. More recently, a caries detecting oral rinse (LumiCare TM ) has been developed which contain proprietary fluorescent starch nanoparticles that allow active initial caries lesions to be detected using a dental curing lamp [109]. Similar to dental photoinitiators, absorption by the endogenous fluorophores or the fluorescent starch nanoparticles leads to excitation of electrons, thermalisation of energy and eventually a return to ground state with the emission of longer wavelength (typically NIR), lower energy radiation.…”
Section: Transillumination and Fluorescencementioning
confidence: 99%
“…A clinical study showed that LC Rinse can distinguish between active caries, inactive caries, and hypomineralization, and can augment caries detection with high sensitivity, specificity, and diagnostic accuracy [162].…”
Section: Fluorescent Starch Nanoparticlesmentioning
confidence: 99%
“…Thank you very much for giving us an opportunity to publish our work [ 1 ] in this high quality and internationally renowned peer-reviewed journal, BDJ Open , and for allowing us to respond to the letter from Dr Chris Longbottom.…”
mentioning
confidence: 99%